Use of IoT Technology in Home Security Monitoring Systems: A Review - Fitriyan, Rahmawati; Muhammad Imran Hamid; Abdul Rajab (Andalas Journal of Electrical and Electronic Engineering Technology, 2024)
Utilizing IoT technology in home security monitoring systems offers an effective solution to improve energy efficiency and security by allowing users to monitor and control electronic devices remotely via the Internet. The basic principles of a smart home include reliable connectivity, device interoperability, stringent security and privacy, and energy efficiency. IoT communications are supported by technologies such as RFID and Wi-Fi to ensure effective wireless data transmission. IoT facilitates connecting new devices without additional installation, using technologies such as Wi-Fi, Barcodes (QR codes), and Bluetooth for various applications. The application of IoT in home security monitoring involves platforms such as Blynk and web servers for remote control, with a focus on data protection and system security. This paper compiles various research and conference-related aspects of IoT, including privacy, educational guidelines, system characterization, innovative grid communications, bridge monitoring, RFID authentication, Wi-Fi technology, Bluetooth communications, smart home applications, and security systems. Topics covered include energy monitoring systems, smart home security, earthquake detection, IoT privacy and security, automation, edge intelligence, and Internet of Things architecture.